Evaluation of neighborhood deprivation and store characteristics in relation to tobacco retail outlet sales violations. - David C Wheeler (Public Library of Science (PLoS), 2021)
Introduction Regulations of the sale of tobacco products to minors have been effective at reducing adolescent tobacco use overall. However, these efforts may not be uniformly enforced in all areas, creating uneven protection against adolescent smoking. Knowledge regarding factors associated with tobacco retail outlet (TRO) violations could help inform better enforcement strategies. Methods In this study, we used Bayesian index regression models to determine if tobacco sales to minors violations across Virginia (2012-2021) were related to store characteristics and neighborhood deprivation and identify geographic areas at significantly elevated risk for violations after adjusting for these factors. Results Results show that there were multiple factors associated with a higher likelihood of tobacco sales violations. Store type was an important factor, as grocery stores and pharmacies had significantly lowered likelihood of violations compared with convenience stores. Being located near another TRO was significantly associated with increased risk of sales to a minor. Neighborhood deprivation was also positively associated with TRO sales violations. Further, there were statistically higher likelihood of sales violations occurring in specific areas (e.g., southwest and southeast) of the state that were not explained by neighborhood deprivation and store attributes. Conclusions Together, results highlight the need to better understand where and why TRO sales violations are occurring in order to improve efforts aimed at monitoring and remediating TRO sales violations.